Breastfeeding and Childhood Obesity Among African Americans. Issue 5 (September 2015) - Hess, Camber; Ofei, Agatha; Mincher, Alicia
Abstract Purpose: Among African Americans, breastfeeding rates are lower and obesity rates higher than other ethnicities in the United States. The objective of this systematic review was to examine the correlation between breastfeeding practices and childhood obesity rates among African Americans in the United States. Study Data Source and Eligibility Criteria: The Cumulative Index to Nursing and Allied Health Literature (CINAHL), PubMed, and Google Scholar were searched using the key words African Americans OR Blacks, Breastfeeding, Childhood Obesity OR Overweight, and Adolescent Obesity OR Overweight. Twelve articles met inclusion criteria and are discussed. Results: No randomized-controlled trials or meta-analyses were found. All studies were observational only. Eight studies found a protective effect of breastfeeding against childhood obesity among African Americans, whereas four other studies were inconclusive. Limitations: Only 12 studies met inclusion criteria for this review, and all studies included other ethnicities in addition to African Americans. More evidence is needed to effectively generalize the results to this population. Conclusions and Implications: More research is needed on the topic; however, current research does suggest a protective effect of breastfeeding against childhood obesity in this high-risk population. Primary care providers and other healthcare workers need to address breastfeeding benefits and barriers among African American women across the continuum of care.